Isoliensinine exerts antitumor effects in lung adenocarcinoma by inhibiting APEX1-driven ROS production - Chen, Cheng; Shu, Chenying; Shen, Dan; Yan, Zhaowei; Liu, Zeyi; Huang, Jian-An (Frontiers in Pharmacology, 2025)
IntroductionLung cancer is considered to be the world’s leading malignancy in morbidity and mortality, and despite great efforts to treat it no effective treatment has yet been found. Isoliensinine is a natural small-molecule drug with potent anti-tumor activity in several cancer cell lines. Here, we have shown that Isoliensinine exhibits anti-tumor activity against lung adenocarcinoma (LUAD) both in vitro and in vivo.MethodsThe biological functions of Isoliensinine in LUAD cells were investigated using CCK8 assay, colony formation, transwell assays and flow cytometry assays. DARTS assay was used to validate Isoliensinine targets screened by site prediction and molecular docking. The in vivo anti-tumor efficacy of Isoliensinine was analyzed in the xenograft tumor model.ResultsThe IC50 of Isoliensinine were 6.98 μM, 17.24 μM and 16.00 μM in H1299, A549, H1650 cell lines while 28.65 μM in BEAS-2B cells. Isoliensinine inhibits the proliferation, migration, invasion of LUAD cells and arrests the cell cycle and promotes LUAD cells apoptosis in vitro. Isoliensinine attenuates tumor growth in a murine xenograft mode. Mechanistically, Isoliensinine interacted directly with APEX1, inhibited APEX1 protein levels, and promoted ROS generation. Knockdown of APEX1 reverses the effect of Isoliensinine on LUAD cells.DiscussionIsoliensinine exerts antitumor effects through inhibition of APEX1 driven ROS production, therefore, Isoliensinine may represent a new drug candidate to be used to treat LUAD.